Surgical site infection after occlusion of the internal carotid artery with a thrombectomy catheter: Five cases. (27th March 2017) - Jennings, A.; Lepage, O.; Mair, T.; Sherlock, C.
Summary: Although rare, guttural pouch mycosis is a potentially life‐threatening disease in the horse. The disease is most commonly treated surgically. One surgical option is occlusion of the internal carotid artery with a combination of ligation and use of a balloon tipped venous thrombectomy catheter. Complications of such treatment are rarely reported. This case series of five individuals describes the appearance, diagnosis and management of medium (>2 weeks) and long‐term (>10 years) complications (including abscess formation, draining sinuses and wound dehiscence) of internal carotid artery occlusion with a venous thrombectomy catheter and management of these surgical site infections. The clinical presentations included swelling and/or discharging tracts in the parotid region. In one horse, an osseous reaction of the basisphenoid bone and penetration of the contralateral guttural pouch by the implant were identified by computed tomography. In all five horses, the surgical site infections were successfully resolved following removal of the venous thrombectomy catheter.